Differential Claudin 3 and EGFR Expression Predicts BRCA1 Mutation in Triple-Negative Breast Cancer. (9th August 2018) - Danzinger, Sabine; Tan, Yen Yen; Rudas, Margaretha; Kastner, Marie-Theres; Weingartshofer, Sigrid; Muhr, Daniela; Singer, Christian F.; ,
Abstract: BRCA-1 mutation-associated triple-negative breast cancer (TNBC) has been hypothesized to exhibit a phenotype that is distinct from non-mutation carriers. We have analyzed immunohistochemically detected cytokeratins 5 and 14, epidermal growth factor receptor (EGFR), claudin (CLDN) 3, 4, and 7, and E-cadherin in 57 TNBC (32 BRCA1 and 8 BRCA2 tumors, 17 WT tumors). Positive staining of CLDN3 and negative EGFR expression in TNBC are associated with a BRCA1 mutation. EGFR and CLDN3 expression was able to predict the presence of BRCA1 mutation (area under curve 0.802, p  < 0.001). This could help in guiding the decision for BRCA testing.